Convenient scoring of deoxyglucose resistance in Neurospora - V. C. Pollard; David D. Perkins (Fungal Genetics Reports, 1994)
Allen et al. (1989 J. Bacteriol. 171:53-58 and personal communication) have described scoring dgr mutants on media prepared by adding filter-sterilized fructose and deoxyglucose solutions to medium that has already been autoclaved. This is inconvenient if tests are to be made on tubed slants, as we prefer to do.